Extraction and characterization of algal oil from Lake Sebu, South Cotabato - Alvin Q. Larida; Jaeven B. Bañaga (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2021)
Algae is rich in storage lipids and fats that can be converted into biodiesel. This study determined the algal oil from Lake Sebu, South Cotabato as biodiesel source. Samples were prepared at varying treatments and ratio with n-Hexane. The algal oil was extracted and efficiency % were determined. FFA% and Acid Number of the oil extract were identified using chemical titration. FTIR was used for Chemical characterization while GC-MS identified fatty acid and other organics. With the constant volume of solvent and by changing the mass of dried algae, the percent yield of oil increases as the solvent to algae ratio increases. Therefore, biomass ratio with n-Hexane should be 1:3. The IR spectra of the oil extract indicated the presence of functional groups such as amine and carbonyl group of amides, methylene, methyl, and alkene. While, GC-MS showed that the fatty acids found can be a potential biodiesel.